2006
DOI: 10.1111/j.1440-1746.2005.04153.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclo‐oxygenase‐2 in gastrointestinal carcinoid tumors

Abstract: Enhanced COX-2 expression was observed in gastrointestinal as well as bronchopulmonary carcinoids and their metastases, especially at the advancing edges of the tumors. Cyclo-oxygenase-2 may play a role in carcinoid progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…This effect may result from the ability to block cyclooxygenase isoforms, COX-1 and COX-2, activity which in turn is linked with carcinogenesis and tumor growth [36]. Of note, it has been reported that COX-2 is expressed in gastrointestinal NETs [37] and in pancreatic endocrine tumors [38], and that treatment with COX-2 inhibitors reduces the viability of carcinoid cells [38]. The potential of aspirin or other COX-2 inhibitors as chemopreventive or active agents in patients diagnosed with NETs, including SI-NETs, has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may result from the ability to block cyclooxygenase isoforms, COX-1 and COX-2, activity which in turn is linked with carcinogenesis and tumor growth [36]. Of note, it has been reported that COX-2 is expressed in gastrointestinal NETs [37] and in pancreatic endocrine tumors [38], and that treatment with COX-2 inhibitors reduces the viability of carcinoid cells [38]. The potential of aspirin or other COX-2 inhibitors as chemopreventive or active agents in patients diagnosed with NETs, including SI-NETs, has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies suggested a role of COX-2 in the pathogenesis and progression of NETs. COX-2 is expressed in pheochromocytoma tissue (Salmenkivi et al 2001) and up-regulated in gastrointestinal and bronchopulmonary carcinoids (Mizuno et al 2006). Moreover, COX-2 up-regulates both expression and bioactivity of chromogranin A in a cell line of rat pheochromocytoma (PC12) (Connolly et al 2007).…”
Section: Pasireotide Plus Cyclooxygenase-2 Inhibitorsmentioning
confidence: 99%
“…Ciclooxigenase-2 (COX-2) is expressed in gastrointestinal carcinoids, especially at the tumours advancing edges and mostly in rectal carcinoids [79], and in some 50% of PETs [80,81]. Cyclooxygenase-2 may therefore play a role in carcinoid progression, and its inhibition through nonsteroidal anti-inflammatory drugs has been shown to inhibit growth of human neuroendocrine tumour cell lines, via G1 cell-cycle arrest [82].…”
Section: Other Possible Therapeutic Targetsmentioning
confidence: 99%